A case report of successful treatment of advanced thymic squamous cell carcinoma with poor performance status using multimodal therapy - Xu, Xianhua; Yan, Xiang; Qin, Yang; Kou, Dan; Huang, Qi; Chen, Qiongcheng; Li, Yejin (Frontiers in Oncology, 2025)
Thymic squamous cell carcinoma (TSCC) is a rare yet aggressive tumor associated with a dismal prognosis. The patient, a 76-year-old male, presented with symptoms of fatigue, bloody sputum and dyspnea. Computed tomography (CT) and positron emission tomography/computed tomography (PET/CT) scans demonstrated a significant mass in the chest, accompanied by metastasis to adjacent lymph nodes. Vascular ultrasound and CT angiography both indicated thrombosis in the jugular, innominate, and left subclavian veins. A CT-guided needle biopsy subsequently confirmed the diagnosis of TSCC. The patient had an Eastern Cooperative Oncology Group (ECOG) Performance Status (PS) score of 4 and exhibited high PD-L1 expression. The treatment plan entailed multiple administrations of low-dose carboplatin via intrapleural injection, infusions of albumin-bound paclitaxel (ABP), and pembrolizumab. Concurrent anticoagulation and nutritional therapy were also provided. A combination of carboplatin and ABP was administered for six cycles, followed by a single cycle of ABP alone. Subsequently, pembrolizumab was administered for ten cycles. After this, pembrolizumab was temporarily discontinued, and radiation therapy was administered to the primary tumor site and mediastinal lymph nodes. Five weeks later, pembrolizumab therapy was resumed. The patient’s PS has recovered to 0, and have survived for 23 months with a good quality of life. This experience suggests that combining pembrolizumab with low-dose chemotherapy drugs could be a beneficial treatment option for patients with advanced TSCC, poor PS, and high PD-L1 expression.